Anatomical derangements after failed PSARP: correlating MRI and operative findings - Amr Abdelhamid AbouZeid; Shaimaa Abdelsattar Mohammad (SpringerOpen, 2021)
Abstract Background Redo surgery for anorectal anomalies (ARA) may be considered a special category of reconstructive surgery with less predictable outcomes. In this report, we studied anatomical derangements in a group of boys following a previously complicated PSARP procedure, in addition to the effect of reoperation on rectifying this distorted anatomy. Results The study included 27 boys who were re-operated after a previous complicated PSARP. Included cases were divided into two groups: group A (14 cases) was referred before colostomy closure with an obviously complicated primary operation, and group B (13 cases) was referred with delayed complications after colostomy closure. Pelvic MRI examinations were performed before reoperation in 19 cases. In nine of these cases, a repeat MRI examination was performed at follow-up after reoperation to study the effect of redo surgery on rectifying the distorted anatomy. Abnormal wide anorectal angle and wide pelvic hiatus were common anatomical derangements after a previously complicated PSARP. An important goal of reoperation was reconstruction of the levator ani behind the anorectum trying to create a more acute anorectal angle and a narrower pelvic hiatus. The success of this corrective step was evaluated by MRI comparing pre- and postoperative measurements that showed a favourable decrease in the values of anorectal angle and hiatal/PC ratio. Improvement of faecal continence was documented after reoperation in 8 out of 10 cases in group B. Conclusion A wide pelvic hiatus was a frequently encountered postsurgical complication after failed PSARP that has most probably resulted from poor reconstruction of the pelvic floor at time of the primary repair. Re-approximation of the split halves of levator ani in the midline behind the anorectum at reoperation can help to correct the distorted internal anatomy and improve bowel control in these cases.